ALELOPATIC EFFECT OF CANOLA EXTRACT (Brassica napus) ON THE SOYBEAN CULTURE TWINNING PHASE - Borella, J.; Leschewitz, R.; Trautenmüller, J. W.; Silva, D. R. O.; Schmidt, D. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Allelopathy is the phenomenon of interactions between plants with release of chemical substances in the environment that provoke stimulatory or inhibitory effects on the germination, growth and development of other plants. The objective of this work was to evaluate the allelopathic effect of canola extract on the germination of soybean cultivars. The experimental design was a randomized block design in a 4x2 factorial arrangement, in which factor A was composed of four soybean cultivars: Monasca, Coodetec 219, BMX Power and BMX Strength, and factor B the concentration of the extract being 0% and 10% . The experiment was conducted on Germitest paper with 50 seeds for each cultivar, with and without aqueous extract of canola, four replicates for each treatment, the rolls containing the seeds were kept in chamber B.O.D. At 25° C. The first germination count, number of germinated seeds, non - germinated seeds, abnormal seedlings, shoot length and radicle, dry mass of shoots and radicle of seedlings were evaluated. The presence of extract influenced the percentage of germinated seeds, but still the cultivar 'BMX Força', presented lower performance with and without the use of the extrado, because the seeds presented less vigor. The cultivar 'BMX Força' and 'BMX Potência' presented deleterious effects when exposed to the canola extract, due to the greater number of abnormal seeds. The cultivar BMX Força demonstrated greater influence on the germination of seeds with the use of the extract and Coodetec 219 showed good performance as cultivar to be used in succession the culture of the canola.